Drona-Chariot: A Medical Equipment Carrier Drone - Sami Firoz Ahmed; Sanskriti Amol Kharsamble; Shivam Santosh Prasad; Rajashree Gadhave (International Journal of Computer Science Languages, 2023)
Caring for trauma victims in harsh environments poses numerous difficulties, especially when a rescue effort is delayed. Human-containable medical equipment may also be consumed by a single victim, making replenishment impossible prior to evacuation, especially in long-term on-site supply scenarios. This project aims to build an unmanned autonomous aerial vehicle that successfully delivers remote places with life-sustaining medical supplies where it is impossible or impractical for vehicles or pedestrians to approach. We are looking forward to simulate the delivery of customizable medical devices such as tourniquets, bandages, analgesics, and blood products. Simulated victims were placed at remote locations. The flight was pre-programmed around the idea of grid coordinates and was flying out of sight on autopilot. A high-altitude drone was used to live- record data, including height, flying time, and route. In numerous instances, drones have successfully and precisely delivered medical supplies more quickly than alternative ways without putting people or manned vehicles at risk. The critical care of military and civilian injuries is aided by this technology.
Keywords: Drone delivery of medications; health care scheduling and logistics; medication quality and compliance; unmanned aerial vehicles for human health